Seasonal Variation in the Chemical Composition of Pomfrets-1 Black Pomfret (Parastromateus niger) - VENKATARAMAN, R.; SOLANKI, K. K.; KANDORAN, M. K. (Fishery Technology, 1968)
Seasonal variations in proximate composition of the different parts such as head, middle, tail and skin of black pomfret (Parastromateus niger) are reported over three years on monthly basis. The lean and fatty conditions of fish are discussed on the basis of spawning period, food and feeding activity, size group appearance and the gonadial maturity of the pomfret.